Plant Diversity Enhances Soil Fungal Diversity and Microbial Resistance to Plant Invasion - Shen, Congcong (Appl Environ Microbiol, 2021)
Interactions and feedbacks between aboveground and belowground biomes are fundamental in controlling ecosystem functions and stability. However, the relationship between plant diversity and soil microbial diversity is elusive. Moreover, it remains unknown whether plant diversity loss will cause the stability of soil microbial communities to deteriorate. To shed light on these questions, we conducted a pot-based experiment to manipulate the plant richness gradient (1, 2, 4, or 8 species) and plant [Symphyotrichum subulatum (Michx.) G. L. Nesom] invasion status. We found that, in the noninvasion treatment, soil fungal diversity significantly and positively correlated with plant diversity, while the relationship between bacterial and plant diversity was not significant. Under plant invasion conditions, the coupling of plant-fungal alpha diversity relationship was enhanced, but the plant-fungal beta diversity relationship was decoupled. We also found significant positive relationships between plant diversity and soil microbial resistance. The observed positive relationships were determined by turnover (species substitution) and nestedness (species loss) processes for bacterial and fungal communities, respectively. Our study demonstrated that plant diversity enhanced soil fungal diversity and microbial resistance in response to plant invasion. This study expands our knowledge about the aboveground-belowground diversity relationship and the diversity-stability relationship. IMPORTANCE Our study newly showed that plant invasion significantly altered relationships between aboveground and belowground diversity. Specifically, plant richness indirectly promoted soil fungal richness through the increase of soil total carbon (TC) without plant invasion, while plant richness had a direct positive effect on soil fungal richness under plant invasion conditions. Our study highlights the effect of plant diversity on soil fungal diversity, especially under plant invasion conditions, and the plant diversity effect on microbial resistance in response to plant invasion. These novel findings add important knowledge about the aboveground-belowground diversity relationship and the diversity-stability relationship.